Magnetic resonance imaging in evaluation of juvenile nasopharyngeal angiofibroma in term of its diagnosis and pattern of spread - ., Puran; Kardam, Narendra Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Juvenile nasopharyngeal angiofibroma (JNA) is a tumor that shows a predictable spreading pattern. This study showed the characteristic MRI findings and its pattern of spread of JNA for diagnosis. Methods: This study consisted of 6 cases of JNA for diagnosis and pattern of spreading by using MRI as modality of choice. Results: The total patients included in study were 6 with age range from 9-20 years and all were male. The classification system used in the study was Radkowski and Onerci system. The tumor showed isointensity to muscle and hyperintensity on T1 and T2 sequences respectively on MR imaging. All lesions had internal signal void regions and showed intense enhancement after IV contrast administration. Diffusion restriction was not an associated features however high values of ADC were noted. The MR angiography of three patients showed blood supply of tumor was mainly from the internal maxillary branch of external carotid artery. The treatment was surgical excision of tumor which was decided on MRI Diagnosis and pattern of Extension described in Radiological report. Conclusions: MRI is a modality of choice for diagnosis and extension of JNA based on clinical and radiological findings, without performing a biopsy.